Src family kinase inhibitor saracatinib (AZD0530) impairs oxaliplatin uptake in colorectal cancer cells and blocks organic cation transporters - Morrow, Christopher J (2010)
Elevated Src Family Kinase (SFK) activity is associated with tumour invasion and metastasis. The SFK inhibitor saracatinib (AZD0530) is currently in Phase II trials in patients including those with colorectal cancer (CRC), where links between SFK activity and poor prognosis are particularly striking. Saracatinib is likely to be used clinically in combination regimens, specifically with 5FU and oxaliplatin in CRC. The aim of this study was to determine the impact of saracatinib on oxaliplatin and 5FU efficacy in CRC cells. Saracatinib did not modulate 5FU efficacy but antagonized oxaliplatin in a schedule specific manner through reduced oxaliplatin uptake via an SFK independent mechanism. Saracatinib resembles the pharmacophore of known organic cation transporter (OCT) inhibitors and reduced oxaliplatin efficacy maximally in cells over-expressing OCT2. These data suggest that oxaliplatin uptake in CRC is attenuated by saracatinib via inhibition of OCT2, a potential consideration for the clinical development of this SFK inhibitor.